The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/08903344211046191
|View full text |Cite
|
Sign up to set email alerts
|

Article: “Too Old” and “Too Cold”: Discomfort Towards Photographs of Breastfeeding Beyond Infancy and Public Breastfeeding in Nova Scotia, Canada

Abstract: Background: Social norms and public perception of breastfeeding are well-established predictors of breastfeeding outcomes; however, little is known about perceptions of breastfeeding beyond infancy or public breastfeeding among the public in Nova Scotia, Canada. Research Aim: To explore public opinion about breastfeeding beyond infancy and public breastfeeding. Methods: In this cross-sectional study participants were recruited from public spaces in Nova Scotia, Canada. Using photo elicitation methods, particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 40 publications
(75 reference statements)
0
3
0
8
Order By: Relevance
“…Of those who were still breastfeeding at 6 months, most noted child's readiness for solids, mother's return to work/school, or a predetermined plan to stop as rationale for breastfeeding cessation; however, the taboo of breastfeeding beyond infancy could also be at play. We recently found that members of the general public were significantly less comfortable viewing breastfeeding photographs of older children, with negative reactions such as "too big to suck breast" elicited from a photograph of a 13-month old breastfeeding at home (Chan and Whitfield 2022). Unfortunately, this taboo may be pervasive even among healthcare professionals: in a recent cross-sectional study in the UK, US, Australia, and Canada (n = 59 581), 49% of women did not share their plan for breastfeeding beyond 12 months with their child's healthcare provider (Keim et al 2022).…”
Section: Extended Breastfeeding Practices In Canadamentioning
confidence: 99%
“…Of those who were still breastfeeding at 6 months, most noted child's readiness for solids, mother's return to work/school, or a predetermined plan to stop as rationale for breastfeeding cessation; however, the taboo of breastfeeding beyond infancy could also be at play. We recently found that members of the general public were significantly less comfortable viewing breastfeeding photographs of older children, with negative reactions such as "too big to suck breast" elicited from a photograph of a 13-month old breastfeeding at home (Chan and Whitfield 2022). Unfortunately, this taboo may be pervasive even among healthcare professionals: in a recent cross-sectional study in the UK, US, Australia, and Canada (n = 59 581), 49% of women did not share their plan for breastfeeding beyond 12 months with their child's healthcare provider (Keim et al 2022).…”
Section: Extended Breastfeeding Practices In Canadamentioning
confidence: 99%
“…To our knowledge, this is the first study that systematically manipulated the presence (and gender) of bystanders in photographs of the same breastfeeding women in the same locations. Although others [ 12 , 13 , 15 ] have examined reactions to images of public breastfeeding, the lack of standardization across photographs (resulting in confounding factors, including the woman’s expression and body position, amount of breast exposure, proximity to bystanders, age of child) limited the ability to draw conclusions about the role of each factor in shaping evaluations of public breastfeeding. In contrast, we can be more certain that the differences observed in the current study are due to the variables of interest.…”
Section: Discussionmentioning
confidence: 99%
“…In Nova Scotia, provincial policy and public health messaging widely promote breast-feeding, but sociocultural norms and structural supports remain inadequate (22) . Nova Scotians are still largely uncomfortable with public breast-feeding (23) , and appropriate lactation spaces are lacking (24) . What is more, public health messages are generally aimed at promoting breast-feeding rather than supporting infant feeding activities and, hence, routinely overlook the unique challenges and required supports of DMF.…”
Section: Methodsmentioning
confidence: 99%